Barriers and facilitators to implement community outreach work and collaboration with partners. (30th September 2020) - Roy, M; Lavoie-Trudeau, É; Benlkhalti, M; Couturier, Y; Lane, J; Clapperton, I; Roy, M A; Bibeau, L; Ouellette, M; Camden, C
Abstract: Background: Community outreach workers support individuals to access health and community services through various form of proximity approaches. Even though community outreach work is present in the province of Quebec (Canada) since the past 40 years, it is still difficult to implement and sustained, especially with families with young children. The aim of this study was to document barriers and facilitators to implement community outreach work, and to describe how such workers collaborate with sectoral (e.g. healthcare) and intersectoral (e.g. municipality, community organizations, schools) partners. Methods: A content analysis was performed on 55 scientific and grey literature documents, and on the transcriptions of 24 individual interviews and 3 focus groups with stakeholders including parents, community outreach workers, healthcare employees, and inter-sectoral partners. Results: This study reveals four categories of barriers and facilitators acting on the implementation of community outreach work: factors related to organizational factors, to the nature of community outreach work, to the intervention with families, and external/uncontrollable factors. With regards to collaboration, community outreach workers collaborate with many partners. Good interprofessional collaboration is achieved with a positive interaction and communication, shared or co-constructed activities for the families, co-intervention with the families, and strategies to be known and intersectoral meetings. Conclusions: Results highlighted that many factors interact and can either influence positively or negatively the opportunity to implement community outreach work. The collaborative practices identified might help maximizing facilitators and overcoming barriers. Advocacy and a better understanding of how to integrate community outreach work within health services while maintaining the workers' flexibility are needed to sustain this practice. Key messages: Advocacy and a better understanding of how to integrate community outreach work within health services while maintaining the workers' flexibility are needed to sustain this practice. Community outreach workers help to reduce inequalities in health.